The relationship between gender and college students' career development - Sauter, Brianna; Fischer, Sarah (My University, 2011)
Although some may think they have control over their future, studies show that one of the most significant influences on career development is the exploration of the environment and the self (Adragna, 2009). The current weak economy may limit a student's financial resources; therefore, choosing a career that is a good fit is more imperative than ever before. This cross-sectional and nonrandom pilot study surveyed 57 male and female freshmen and sophomore college students at a small midwestern university on their past experiences that have influenced their career choices as well as their future career aspirations. We predicted that there would be moderate differences in gender regarding college students' career development based on current literature. Survey data was statistically analyzed using cross-tabulations, mean comparisons, independent t-tests, and a reliability analysis. Results indicated that there were no significant gender differences, but moderate gender differences were found within certain variables. Males considered their parents' career as more of an influence than females did, but did not consider many other factors as very influential (e.g., the media or their parents in general). Gender differences were also found within their current major and ideal career choice. Implications for practitioners are that support, guidance, and resources should be provided early, but children should also be allowed to make autonomous decisions. Future research would benefit from a large, randomized national sample along with rephrasing the negatively correlated dependent variables.
Keywords: Vocational guidance; Career development; Employment--Psychological aspects